V-ATPase modulates exocytosis in neuroendocrine cells through the activation of the ARNO-Arf6-PLD pathway and the synthesis of phosphatidic acid - Wang, Qili; Wolf, Alexander; Ozkan, Sebahat; Richert, Ludovic; Mely, Yves; Chasserot-Golaz, Sylvette; Ory, Stéphane; Gasman, Stéphane; Vitale, Nicolas (Frontiers in Molecular Biosciences, 2023)
Although there is mounting evidence indicating that lipids serve crucial functions in cells and are implicated in a growing number of human diseases, their precise roles remain largely unknown. This is particularly true in the case of neurosecretion, where fusion with the plasma membrane of specific membrane organelles is essential. Yet, little attention has been given to the role of lipids. Recent groundbreaking research has emphasized the critical role of lipid localization at exocytotic sites and validated the essentiality of fusogenic lipids, such as phospholipase D (PLD)-generated phosphatidic acid (PA) during membrane fusion. Nevertheless, the regulatory mechanisms synchronizing the synthesis of these key lipids and neurosecretion remain poorly understood. The vacuolar ATPase (V-ATPase) has been involved both in vesicle neurotransmitters loading and in vesicle fusion. Thus, it represents an ideal candidate to regulate the fusogenic status of secretory vesicles according to their replenishment state. Indeed, the cytosolic V1 and vesicular membrane-associated V0 subdomains of V-ATPase were shown to dissociate during stimulation of neurosecretory cells. This allows subunits of the vesicular V0 to interact with different proteins of the secretory machinery. We show here that V0a1 interacts with the Arf nucleotide-binding site opener (ARNO) and promotes the activation of the Arf6 GTPase during exocytosis in neuroendocrine cells. When the interaction between V0a1 and ARNO was disrupted, it resulted in the inhibition of PLD activation, the synthesis of phosphatidic acid during exocytosis, and changes in the timing of fusion events. These findings indicate that the separation of V1 from V0 could function as a signal to initiate the ARNO-Arf6-PLD1 pathway and facilitate the production of phosphatidic acid, which is essential for effective exocytosis in neuroendocrine cells.